2018
DOI: 10.1002/jpln.201800012
|View full text |Cite
|
Sign up to set email alerts
|

Biosolubilization of phosphorus from rock phosphate and other P fertilizers in response to phosphate solubilizing bacteria and poultry manure in a silt loam calcareous soil

Abstract: ‘Phosphate solubilizing bacteria' (PSBs) are able to release unavailable P from native and applied P sources into plant‐available soil pool through their solubilizing and acidifying effects. The effects of three indigenous and one exotic PSBs on P solubilization from different P sources, plant biomass production, and P‐uptake efficiency of maize (Zea mays L.) were examined in an incubation and greenhouse study. For incubation study, surface (0–15 cm) soil was collected from an arable field (Inceptisols) and am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 32 publications
(51 reference statements)
0
7
0
Order By: Relevance
“…Such changes would suggest that membrane stability is affected and that these structures would no longer function properly. Another study conducted by Abbasi and Manzoor (2018) showed that the RWC of wheat plants decreased under P deficiency and salt stress. For the same species, the combination of water and salt stress highly affected the genes that are responsible and related to growth and different trait indicators of nitrogen metabolism (nitrogen content, stable nitrogen isotope composition, glutamine synthetase, and nitrate reductase activities) and photosynthetic carbon metabolism (Yousfi et al, 2016).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Such changes would suggest that membrane stability is affected and that these structures would no longer function properly. Another study conducted by Abbasi and Manzoor (2018) showed that the RWC of wheat plants decreased under P deficiency and salt stress. For the same species, the combination of water and salt stress highly affected the genes that are responsible and related to growth and different trait indicators of nitrogen metabolism (nitrogen content, stable nitrogen isotope composition, glutamine synthetase, and nitrate reductase activities) and photosynthetic carbon metabolism (Yousfi et al, 2016).…”
Section: Discussionmentioning
confidence: 98%
“…The application of RP seems to be an affordable and environment-friendly solution to replace chemical P fertilizers. Additionally, the application of organic fertilizers often did not show the same positive effects as mineral fertilizers (Abbasi and Manzoor, 2018). The utilization of phosphate-solubilizing bacteria (PSB) in combination with RP could increase the level of plant-available P in soils (Wahid et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In vitro investigations of microbial weathering have demonstrated that the solubilizing ability of PSB and KSB is mainly affected by factors such as the concentration of soluble P or K, C and N sources, and pH (Parmar and Sindhu, 2013;Musarrat and Khan, 2014). In the same way, soil experiments and field trials indicate that N fertilization, organic amendment, and lime addiction directly influence the effectiveness or abundance of solubilizing organisms (Adnan et al, 2017;Zheng et al, 2017;Kaleem Abbasi and Manzoor, 2018;Zheng et al, 2019). Therefore, these factors can be modulated to enhance bacterial solubilization of minerals.…”
Section: Concomitant Use Of Rocks and Weathering Bacteria As Fertilizmentioning
confidence: 99%
“…Since the first reports of 70 years ago, PSB benefits have been demonstrated for different and agronomically relevant crops. The main observed effects in crop production include the reduction in the application of traditional fertilizers (Sundara et al, 2002), the improvement on the efficacy of low-cost RP, the reduction of P losses in the soil, and the improvement of plant development (Kaleem Abbasi and Manzoor, 2018). In Table 1, different studies were summarized considering the concomitant effect of PSB inoculation with the RP soil amendment.…”
Section: Weathering Bacteria and P Availabilitymentioning
confidence: 99%
“…The role of PSM such as bacteria and fungi in increasing soil P available fraction has been widely investigated by many researchers (Manzoor et al, 2017;Adhikari and Pandey, 2019;Faried et al, 2019). Phosphate solubilizing bacteria are the most known and studied microorganisms for their potential to solubilize P. These microbes participate in bio-geochemical P cycling mainly through solubilization of inorganic forms of P and mineralization of organic ones (Manzoor et al, 2017;Abbasi and Manzoor, 2018). The microbial solubilization of insoluble P has been often attributed to organic acid excretion (i.e., lactic acid, succinic acid, acetic acid, fumaric acid, etc.)…”
Section: Phosphate Solubilising Microorganisms Stimulate Bnf In Grainmentioning
confidence: 99%